Analisis Peran Pengawas Penyidikan Dalam Implementasi Elektronik Manajemen Penyidikan (E-MP) Di Direktorat Reserse Narkoba Polda Bengkulu - Muhammad Azim; Slamet Widodo; Praningrum Praningrum (Universitas Bengkulu, 2021)
This research was conducted to find out how the implementation of Elektronik Manajemen Penyidikan (E-MP) in the Bengkulu Regional Police Narcotics Directorate, and what factors are indicative of personnel using this system, then how the role of supervision (internal) investigation in its optimization. This research was conducted through a qualitative approach and in its presentation the writer used exploratory methods with a population of 30 investigative personnel at the Bengkulu Regional Police's Narcotics Detective Directorate and hopes to be able to describe the object of research as it is. Based on the results of the study it can be concluded that the implementation of Elektronik Manajemen Penyidikan (E-MP) at the Bengkulu Police Narcotics Investigation Directorate has been going very well with adequate facilities support even though it has not been optimal and is still under development. Then related to the personnel indication personnel must use this application, because the E-MP system is an embodiment of the 2015-2019 National Police Strategic Plan intended for investigators/ assistant investigators in the investigation management system as well as a database of criminal cases to realize transparency, and (internal) surveillance of investigations in accordance with Perkap Number 06 of 2019 concerning Criminal Action Investigation. So that the implementation of E-MP can run optimally, it is necessary to maximize the support of infrastructure, improved content on the application so that it can accommodate all Police duties and in the implementation of supervision through the E-MP is not only limited to the quantity but needs to be examined the quality of the product documents produced, then an SOP is made in the implementation of access, input and activities through this application and can immediately be used as a reference in evaluating performance. The limitation of this study is more due to the fact that when the study was conducted there was a change of leadership within the Bengkulu Police Narcotics Investigation Directorate, thereby also affecting respondent responses regarding filling questionnaire and interview as a reference for the results of this study.